2018
DOI: 10.1371/journal.pone.0205419
|View full text |Cite
|
Sign up to set email alerts
|

Developing a learning health system: Insights from a qualitative process evaluation of a pharmacist-led electronic audit and feedback intervention to improve medication safety in primary care

Abstract: IntroductionDevelopments in information technology offer opportunities to enhance medication safety in primary care. We evaluated the implementation and adoption of a complex pharmacist-led intervention involving the use of an electronic audit and feedback surveillance dashboard to identify patients potentially at risk of hazardous prescribing or monitoring of medicines in general practices. The intervention aimed to create a rapid learning health system for medication safety in primary care. This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 43 publications
3
65
0
1
Order By: Relevance
“…The second implication returns to the point made by Jefferies et al [ 15 , 16 ], which highlights the importance of communication between networks. It is the experience here that a significant element of the work was hidden to maintain relationships between members of the implementation network.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The second implication returns to the point made by Jefferies et al [ 15 , 16 ], which highlights the importance of communication between networks. It is the experience here that a significant element of the work was hidden to maintain relationships between members of the implementation network.…”
Section: Discussionmentioning
confidence: 76%
“…This was most noticeable in terms of the effect the infrastructure required for implementation [ 19 ]. The process experienced here hints towards the local health and social care community operating at capacity with limited resource availability or flex to perform the work necessary for successful implementation as the required facets were created directly by the implementation network [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dashboard, that is refreshed daily, provides feedback about identified patients exposed to potentially hazardous prescribing and inadequate blood-test monitoring. A previous qualitative study specifically explored the ways in which the full SMASH intervention was adopted, implemented and embedded in general practices and revealed that the success of this work was critically dependent upon the pivotal role of the pharmacist and how they and other clinicians and staff members interacted with each other to create a learning health system [18]. This previous qualitative study focused on the ways in which the intervention was integrated into practice and drew upon Normalisation Process Theory to understand this process [19].…”
Section: Introductionmentioning
confidence: 99%
“…Normalisation process theory is based on the premise that ‘interventions become routinely embedded in their organisational and professional contexts as the result of people working, individually and collectively, to implement them’ 20 . Although there is much overlap between implementation theories, 21 NPT was chosen from other implementation frameworks as NPT offers a comprehensive explanation of implementation processes 22 and a valuable approach to researching SBE with participants in different contexts and at different stages of the process 23,24 …”
Section: Methodsmentioning
confidence: 99%